Efficacy of Intensive Inpatient Therapy in Infants with Congenital Muscular Torticollis Involving the Entire Sternocleidomastoid Muscle - Dong Rak Kwon; Sung Cheol Cho (MDPI AG, 2023)
The efficacy and frequency of physiotherapy in the prognosis of congenital muscular torticollis (CMT) that involves the entire sternocleidomastoid (SCM) muscle continues to be unclear. This study investigated the therapeutic effect of intensive inpatient therapy given to infants with CMT that involves the whole SCM using clinical measurements and ultrasound (US). This study included 54 infants (27 boys and 27 girls; mean corrected age of 18.57 days) evaluated for CMT at our outpatient clinic from January 2014 to May 2021. The included patients were divided into three groups (groups 1, 2, and 3). Patients in group 1 underwent outpatient treatment 12 times. Patients in groups 2 and 3 underwent therapeutic exercise followed by US diathermy with microcurrent twice daily for 1 or 2 weeks, respectively. Passive range of motion of the cervical rotation (PCRROM) and SCM thickness were evaluated pre- and post-treatment. Among the three groups, the demographic data at baseline were not significantly different, SCM thickness and PCRROM were significantly decreased/increased at post-treatment compared to pre-treatment (p < 0.05), mean PCRROM change was significantly greater in group 3 (p < 0.05), and mean SCM thickness reduction between pre-treatment and 3 months post-treatment was significantly greater in groups 2 and 3 (p < 0.05). Therefore, intensive inpatient therapeutic exercise and US diathermy with microcurrent may enhance the prognosis of CMT involving the entire SCM muscle.